A Constructivist Leader Avoids the Bankruptcy of an Emblematic Company and the Deepening of Deindustrialization in Europe: Lessons From a Case Study - Lopes, Albino; Romana, Fernando Acabado; Barrosa, Luis; Martins, Antonio Eduardo (Archives of Business Research, 2024)
Confronting a complex reality always causes a mixture of shock that continues, even after acceptance. The moment Bertrand Martin takes over C.M.M. Sulzer-France in 1984, the company is in the disaster situation. With the Naval Construction crisis, the order book quickly ran out, the stock warehouses were full, and people’s morale was at a level close to exhaustion. Everyone expected either closure or, at the very least, a massive collective dismissal. B. Martin’s position surprises everyone and everything, equivalent to a real electroshock, according to his own expression. In a staff meeting, called by him to “say what he came for”, B. Martin (or a member of his management team) holds back and does not even formulate a word that evokes “solutions”. Faced with the dramatic events that the company was experiencing, B. Martin says he is at this staff meeting to hear… solutions, as an alternative to closure or massive layoffs. Rarely have words like these been heard in companies in a country accustomed to a hierarchical organizational culture and job cuts in response to crises. Voluntary problem-solving groups, involving more than 300 people from all hierarchical levels, developed a plan with 450 measures. The workers’ assembly votes on the plan unanimously. In a short time, the company changes radically and comes out of the red, accepting a difficult challenge, associated with an order for two large power plant engines, for China, previously considered unrealizable. The dynamics introduced into the company become proverbial with unusual repercussions throughout France. The case seems to fit more into the order of counter factuality than a plausible situation. Four orders of reasons seem to have contributed to the novelty of the director general’s communication: (1) A general director who, instead of starting by presenting a speech of hope (to create a climate of positive expectation), as is customary to do, exposes the naked reality for everyone to observe. (2) A leader who says he has no solutions but was available to listen to the solutions to be found within the organization. (3) An entrepreneur who knew how to listen to himself and listen to what he would call a “crazy dream” that mobilized the talents of each subject. (4) A people engineer who knew how to intuit, as an organizational reference, the thirst for collectively shared change and which would allow 70% of all four hundred proposals from the working groups to be carried out in six months. The constructivist transformational leadership of this leader, unlikely given the context, Bertrand Martin, made the difference, in a situation where “hope seemed to have disappeared”, in the words of Dante, in the “Divine Comedy” – sequel to Inferno.